The Life in Law of George Paterson Barton QC - Elias, Sian (Victoria University of Wellington Law Review, 2012)
This address was given by the Chief Justice of New Zealand, Dame Sian Elias, on the occasion of the special sitting of the High Court in Wellington to honour Dr George Barton QC on Wednesday 6 July 2011.